Comparison of Quality of Life among Adolescents with and without Diabetes in Gujrat, Pakistan - Iqbal, Sonia; Ayaz, Saeed Bin; Rahman, Fawad; Ejaz, Saman; Waheed, Laiba; Amjad, Ayesha (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the quality of life among adolescents with and without diabetes and explore the association of age and gender with diabetes.Study Design: Cross-sectional comparative study.Place and Duration of Study: Different Clinics and Hospitals, of District, Gujrat Pakistan, from Sep 2020 to Mar 2021.Methodology: Adolescents with diabetes who had an HbA1C level of ≥6.5%, and age-matched, healthy adolescents as controls were included. The adolescents with diabetes were sub-grouped into early and late adolescents based on age (10-14 years and 15-19 years, respectively). Youth Quality of Life Questionnaire was used as the investigative tool. Results: Twenty-nine adolescents (mean age: 14.2±2.9 years) were in the Diabetes-Group, and 356 adolescents (mean age: 14.8±2.7 years) were in the Control-Group. The Control-Group had significantly better mean scores in each domain than the Diabetes-Group (p